Leptospira interrogans biofilm formation in Rattus norvegicus (Norway rats) natural reservoirs. - Ana Amélia Nunes Santos; Priscyla Dos Santos Ribeiro; Geórgia Virgínia da França; Fábio Neves Souza; Eduardo Antônio Gonçalves Ramos; Cláudio Pereira Figueira; Mitermayer G Reis; Federico Costa; Paula Ristow (Public Library of Science (PLoS), 2021)
Rattus norvegicus (Norway rat) is the main reservoir host of pathogenic Leptospira, the causative agent of leptospirosis, in urban environments. Pathogenic Leptospira forms biofilms in the environment, possibly contributing for bacterial survival and maintenance. Nonetheless, biofilms have not yet been studied in natural animal reservoirs presenting leptospiral renal carriage. Here, we described biofilm formation by pathogenic Leptospira inside the renal tubules of R. norvegicus naturally infected and captured in an urban slum endemic for leptospirosis. From the 65 rats carrying Leptospira in their kidneys, 24 (37%) presented biofilms inside the renal tubules. The intensity of leptospiral colonization in the renal tubules (OR: 1.00; 95% CI 1.05-1.1) and the type of occlusion pattern of the colonized renal tubules (OR: 3.46; 95% CI 1.20-9.98) were independently associated with the presence of Leptospira biofilm. Our data showed that Leptospira interrogans produce biofilms during renal chronic colonization in rat reservoirs, suggesting a possible role for leptospiral biofilms in the pathogenesis of leptospirosis and bacterial carriage in host reservoirs.